Fashioning the Emotional Self: The Dutch Statesman Rutger Jan Schimmelpenninck (1761-1825) and the Cult of Sensibility - Hagen, Edwina (BMGN - Low Countries Historical Review, 2014)
This article proposes a combined perspective of Greenblatt’s famous concept of ‘self-fashioning’ and Reddy’s well-known theory of ‘emotives’ as a possible new approach to the study of Dutch political culture, and more specifically to political figures. Exploring emotions as an aspect of public self-fashioning, it focuses on the Dutch statesman Rutger Jan Schimmelpenninck as an early modern example. Schimmelpenninck, like his fellow revolutionaries, radicals and moderates, was familiar with the vocabulary of the French political version of sensibility (Reddy’s sentimentalism) with its strong emphasis on sincerity. However, in contrast to France, emotions in Dutch revolutionary politics remained of crucial importance thanks to the emergence of an alternative calm style developed by the moderates, most fully embodied by Schimmelpenninck. Helped in part by his republican friends, he promoted himself by stressing his ‘meekness’ as the virtue of his political leadership, but it was precisely this aspect of his public persona that his Dutch political enemies equated with ‘weakness’. This article is part of the special issue ’Batavian Phlegm?’. Emotionele ‘self-fashioning’. De Nederlandse staatsman Rutger Jan Schimmelpenninck (1761-1825) en de cultus van het gevoel Dit artikel beoogt een nieuwe impuls te geven aan het historisch onderzoek naar de Nederlandse politieke cultuur door aandacht te vragen voor de historiografische verrijking die mogelijk besloten ligt in een verbinding van Greenblatt’s beroemde concept self-fashioning en Reddy’s bekende theorie van de emotives. Als eerste verkenning van de mogelijkheden van deze gecombineerde benadering wordt een analyse gemaakt van de manier waarop de Nederlandse staatsman Rutger Jan Schimmelpenninck emoties inzette voor de cultivering van zijn politieke imago. Schimmelpenninck was net als zijn mede-revolutionairen goed op de hoogte van de Frans-revolutionaire cultus van het gevoel (door Reddy sentimentalisme genoemd) maar ontwikkelde als Nederlandse moderate republikein een eigen, kalme en gematigde stijl. Geholpen door zijn politieke vrienden promootte hij zichzelf als een politiek leider met een uitgesproken zachtaardige natuur. Zijn binnenlandse opponenten grepen juist deze (voorgewende) eigenschap aan als het bewijs van zijn beginselloze zwakte. Dit artikel maakt deel uit van het themanummer ’Batavian Phlegm?’.